Optimization of Squeeze Casting Process Parameters on AA8011 Based Hmmcs Under NaCl Environment - S. Senthil Kumar; G. Karthikeyan; K. Panneer Selvam (Archives of Metallurgy and Materials)
The present research computes the impact of process parameters of squeeze casting on AA8011/Si3N4/ZrO2 Hybrid Metal Matrix Composites (HMMCs). The melting temperatures (700 to 800°C), Si3N4 + ZrO2 (5 to 15 wt.%) and stirring speed (550 to 750 rpm) were selected as parameters for input. The AA8011 HMMCs were fabricated as per the combination of L9 input parameters, and they were subjected to Energy Dispersive X Ray Analysis (EDAX) and Scanning Electron Microscope (SEM) tests to compute the presence of wt.% of matrix and reinforcements and to confirm the uniform distribution of Si3N4 + ZrO2 in matrix AA8011. Besides, fabricated composites were subjected to tensile and micro hardness test after subjecting to Salt spray test (3.5% NaCl, 120 hours exposing duration and 1.2 kg/cm2 spray pressure) for computing the Ultimate Tensile Strength (UTS) and micro hardness. The Grey Relational Analysis (GRA) was employed for optimizing process parameters of squeeze casting on AA8011 based composites. The EDAX test results confirms that the increasing wt.% of silicon nitride and zirconium dioxide reinforcements enhances the presence of elements such as Si, N, Zr and O in manufactured composites. The higher dense reinforcements are uniformly distributed in the matrix AA8011 at the blend of input parameters of AA8011 composite. Based on the Taguchi approach, the medium level of melting temperature (750°C), higher level of wt.% of Si3N4 and ZrO2 reinforcements (15 wt.%) and higher level for speed of stirring (750 rpm) is the optimized combination parameters of squeeze casting for UTS and microhardness are identified. Based on the GRA technique, the influencing sequence are identified for squeeze casting process parameters are wt.% of Si3N4 + ZrO2 reinforcements, stirring speed and melting temperature for both UTS and Micro hardness. The contribution percentage of melting temperature, wt.% of reinforcements and stirring speed are 20.26%, 48.102% and 29.23% respectively. The confirmation test was done for optimized input parameters and it exhibit 56% higher UTS and 48.2% higher micro hardness of than AA8011 matrix material.